Tailoring Defects in Hard Carbon Anode towards Enhanced Na Storage Performance - Ruiqi Dong; Feng Wu; Ying Bai; Qinghao Li; Xiqian Yu; Yu Li; Qiao Ni; Chuan Wu (Energy Material Advances, 2022)
Hard carbon (HC) anodes show conspicuously commercialized potential for sodium-ion batteries (SIBs) due to their cost-effectiveness and satisfactory performance. However, the development of hard carbon anodes in SIBs is still hindered by low initial Coulombic efficiency (ICE) and insufficient cyclic stability, which are induced by inappropriate defects in the structure. Herein, we introduce a simple but effective method to tailor the defects in HC by the chemically preadsorbed K+. The soft X-ray absorption spectroscopy at the C K-edges reveals that K+ can anchor on the hard carbon via C-O-K bonds, occupying the irreversible reactive sites of Na+. Therefore, the irreversible capacity caused by some C-O bonds can be reduced. Moreover, the preadsorbed K+ can induce the rearrangement of carbon layers and lead to a high graphitization structure with fewer defects and large interlayer spacing, which not only improves the structural stability and electrical conductivity of the HC anode but also facilitates fast Na+ diffusion. Therefore, the as-obtained optimized anode demonstrates a higher ICE with better cyclic stability and superior rate capacities compared with the anode without preadsorbed K+. This work indicates that K+ preadsorbed into hard carbon is a practicable alternative to enhance the Na storage performances of HC anodes for SIBs.